The Effect of the Implementation of Education Policy Based on Policy Attitudes on the Competency of Vocational High School Graduates in Jayapura Regency, Papua Province - Tri Bowo Budi Santoso (Syntax Corporation Indonesia, 2025)
The low absorption of Vocational High School (SMK) graduates in the world of work is a challenge for all parties in making vocational education policies. The same condition is also experienced in Papua Province, especially with the policy of regional expansion. Research on education policies in the competency standards of vocational school graduates needs special attention, so that vocational school graduates in Papua, especially in Jayapura Regency, have competence, in accordance with the needs of the world of work, which can improve the welfare of the Papuan people and regional development. In this study, a quantitative approach with descriptive and inferential statistical analysis was used to reveal the influence of the implementation of education policies based on the attitudes of policy makers on the competence of vocational school graduates in Jayapura Regency, Papua Province. The survey respondents totaled 252 people, consisting of the Government, private sector, and civil society. The results of the study show that the implementation of the policy has gone well, as evidenced by high categorization, which means that the implementation of the competency policy for vocational school graduates has gone well in Jayapura Regency. The implementation of policies through the MSN approach shows the greatest influence on competency 4, namely responsible behavior in reflecting, taking initiative and designing strategies for learning and self-development, as well as being used to adapting and maintaining commitment to achieve goals with a contribution of 48.4%. The factors that hinder implementation occur because the affective and conative aspects of attitudes are still in the average category even though there is a contribution of policy makers' attitudes to the implementation of the approach of 51.7% and there is a very significant influence of attitudes towards policy implementation through the MSN approach (F=267,776; p=0.00). This shows that policy implementation can be carried out more optimally if there is a more positive attitude from policy makers towards the competence of vocational school graduates, especially improvements in affective and contive aspects.